Adding Azithromycin to Cephalosporin for Cesarean Delivery Infection Prophylaxis: A Cost-Effectiveness Analysis. Issue 6 (December 2017) - Skeith, Ashley E.; Niu, Brenda; Valent, Amy M.; Tuuli, Methodius G.; Caughey, Aaron B.
Abstract : OBJECTIVE: To investigate the cost-effectiveness of adding azithromycin to standard cephalosporin regimens of cesarean delivery prophylaxis by considering the maternal outcomes in the current and potential subsequent pregnancies. METHODS: A cost-effectiveness model was created using TreeAge to compare the outcomes of using azithromycin–cephalosporin with cephalosporin alone in a theoretical cohort of 700, 000 women, the approximate number of nonelective cesarean deliveries annually in the United States that occur during labor or after membrane rupture. Outcomes examined included endometritis, wound infection, sepsis, venous thromboembolism, and maternal death in the current pregnancy and uterine rupture, cesarean hysterectomy, and maternal death in subsequent pregnancies, including cost and quality-adjusted life-years for both pregnancies. Probabilities, utilities, and costs were derived from the literature, and a cost-effectiveness threshold was set at $100, 000 per quality-adjusted life-year. Sensitivity analyses were used to determine the robustness of our results. RESULTS: Compared with cephalosporin alone for prophylaxis, our model showed 16, 100 fewer cases of endometritis, 17 fewer cases of sepsis, eight fewer cases of venous thromboembolism, and one fewer maternal death with azithromycin–cephalosporin. Additionally, this strategy prevented 36 uterine ruptures and four cesarean hysterectomies in the subsequent pregnancy. Overall, the addition of azithromycin led to both lower costs and higher quality-adjusted life-years when compared with standard cephalosporin prophylaxis. In sensitivity analysis, we found that as long as the cost of azithromycin remained below $930 (baseline cost $27), it was cost-effective. CONCLUSION: For women who undergo cesarean delivery in labor or after membrane rupture, compared with cephalosporin alone, the addition of azithromycin to cesarean delivery infection prophylaxis is less costly and leads to better maternal outcomes in the index delivery and subsequent deliveries. These findings support the use of prophylactic azithromycin at the time of cesarean delivery. Abstract : For women who undergo cesarean delivery after labor or membrane rupture, the addition of azithromycin to cephalosporin infection prophylaxis is cost-effective.